2010
DOI: 10.3238/arztebl.2010.0231
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Neglect

Abstract: At the beginning of the 21(st) century, well-established normative structures are in place to protect children against abuse and neglect, and the available help from social organizations can also have a preventive effect. Further improvements will depend on interdisciplinary coordination and better training of specialists in all of the involved disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
(4 reference statements)
0
10
0
3
Order By: Relevance
“…[3][4][5][6][7][8][9] Severe diabetic wounds could lead to amputation. 10 Diabetes can be divided into four main types: Type Ⅰ diabetes is caused by the autoimmune be destroyed of β-cells in the pancreas, eventually leading to reduction of insulin production; 11,12 Type Ⅱ diabetes is closely associated with insulin resistance and subsequent decompensation of pancreatic β-cells (including pancreatic β-cell mass loss and β-cell dysfunction); 13 Gestational diabetes occurs during pregnancy and causes glucose intolerance; 14 other diabetes are resulted by specific genetic defects of beta-cell function, illness of the pancreas, drugs or chemicals, etc. 15…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Severe diabetic wounds could lead to amputation. 10 Diabetes can be divided into four main types: Type Ⅰ diabetes is caused by the autoimmune be destroyed of β-cells in the pancreas, eventually leading to reduction of insulin production; 11,12 Type Ⅱ diabetes is closely associated with insulin resistance and subsequent decompensation of pancreatic β-cells (including pancreatic β-cell mass loss and β-cell dysfunction); 13 Gestational diabetes occurs during pregnancy and causes glucose intolerance; 14 other diabetes are resulted by specific genetic defects of beta-cell function, illness of the pancreas, drugs or chemicals, etc. 15…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the failure to diagnose the maltreatment may, in itself, present problems of proof since the identification of physical abuse can be difficult (27). It has been outlined that many missed opportunities for diagnosing physical abuse can materialize for professionals whose functions involve regular contacts with children and adolescents, as well as those who may only occasionally come into contact with them in their work (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Pokroy et al ( 18 ), they investigated self-inflicted factitious conjunctivitis in conscripted soldiers and found that all cases showed inferior bulbar conjunctival hyperemia with a surprisingly quite superior bulbar conjunctiva similar to our case. Therefore, ocular injuries involving the more accessible inferior and nasal aspects of the eye should alert ophthalmologists that these injuries might be self-inflicted ( 19 ). Munchhausen’s by proxy ( 20 , 21 ) as a liability had been excluded due to the illiterate and worried nature of both parents who appeared in the interview with the child, also, there was no family history of similar conditions in their other children.…”
Section: Discussionmentioning
confidence: 99%